Mortality Associated with Tuberculosis Meningitis in HIV Infected Patients and Non-HIV Infected Patients: Tuberculosis Meningitis in Infected and Non-HIV Infected Patients - Haji, Salma; Afzal, Munir; Akram, Waseem; Ahmed, Atif; Memon, Beenish; Kumari, Monika (Pakistan Journal of Health Sciences, 2025)
Human Immunodeficiency Virus (HIV) infection significantly worsens Tuberculosis meningitis (TBM) outcomes, leading higher mortality rate in HIV-positive patients compared to HIV-negative individuals. Objectives: To find out the frequency of HIV Infected Patients with TBM and their outcome as mortality and to compare their mortality of TBM without HIV infection. Methods: This cross-sectional-observational study was conducted at Jinnah Postgraduate Medical Center Karachi, from September 2020 to October 2024. All patients diagnosed with TBM on clinical findings and Cerebrospinal Fluid analysis as TBM were admitted an HIV test was carried out and a CD4 cell count was done in HIV-positive patients. Treatment with Anti-Tuberculosis Therapy and Antiretroviral Therapy was done, the outcome as mortality was recorded up to 1 year and results were analyzed by SPSS version 26.0. Results: A total of 260 patients were enrolled who presented with TBM. The mean age was 39 ± 12.7 years. 20/260 (7.69%) were HIV positive and 240/260 (92.3%) were HIV negative TBM patients. 130/240 (54.16%) were male and 110/240 (45.93%) were female in HIV-negative and HIV-positive TBM 12/20 (60%) were male and 8/20 (40%) patients were female. age in HIV-positive patients was 32.5 ± 5.5 and 38.5 ± 6 in HIV-negative patients. 13/20 (65%) HIV-positive patients expired and 55/240 (22.9%) of HIV-negative patients expired. Conclusions: It was concluded that HIV Infected patients in our setup were increasing and had a high mortality rate as compared to HIV-negative patients of TBM and TBM patients presented in stage 3 had high mortality in both HIV-positive and HIV-negative patients.